2021
DOI: 10.1002/acn3.51300
|View full text |Cite
|
Sign up to set email alerts
|

Isradipine plasma pharmacokinetics and exposure–response in early Parkinson’s disease

Abstract: Objectives Isradipine is a dihydropyridine calcium channel inhibitor that has demonstrated concentration‐dependent neuroprotective effects in animal models of Parkinson’s disease (PD) but failed to show efficacy in a phase 3 clinical trial. The objectives of this study were to model the plasma pharmacokinetics of isradipine in study participants from the phase 3 trial; and, to investigate associations between drug exposure and longitudinal clinical outcome measures of PD progression. Methods Plasma samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
6
26
0
Order By: Relevance
“…Thus, the results of the clinical trial did not support the hypothesis that isradipine, at this dosage, can slow the progression of PD [143]. One possible explanation for this result is that the bioavailability of isradipine at the used dosage was not sufficient to target the Ca V 1.3 channels in neurons, but a direct empiric measure of effective local drug engagement is not feasible [143,144]. This explanation has been further supported by modeling the pharmacokinetics of isradipine based on the trial data, indicating that the critical threshold for therapeutic efficacy might have been reached only transiently and for a short time [144].…”
Section: Vgcc Inhibitors In the Treatment Of Parkinson's Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the results of the clinical trial did not support the hypothesis that isradipine, at this dosage, can slow the progression of PD [143]. One possible explanation for this result is that the bioavailability of isradipine at the used dosage was not sufficient to target the Ca V 1.3 channels in neurons, but a direct empiric measure of effective local drug engagement is not feasible [143,144]. This explanation has been further supported by modeling the pharmacokinetics of isradipine based on the trial data, indicating that the critical threshold for therapeutic efficacy might have been reached only transiently and for a short time [144].…”
Section: Vgcc Inhibitors In the Treatment Of Parkinson's Diseasementioning
confidence: 91%
“…One possible explanation for this result is that the bioavailability of isradipine at the used dosage was not sufficient to target the Ca V 1.3 channels in neurons, but a direct empiric measure of effective local drug engagement is not feasible [143,144]. This explanation has been further supported by modeling the pharmacokinetics of isradipine based on the trial data, indicating that the critical threshold for therapeutic efficacy might have been reached only transiently and for a short time [144]. The administration of higher doses is discouraged because of the secondary cardiovascular effects that isradipine may induce.…”
Section: Vgcc Inhibitors In the Treatment Of Parkinson's Diseasementioning
confidence: 99%
“…In humans, the ongoing phase III clinical study STEADY-PD is investigating the potential of the LTCC blocker isradipine for treatment of PD. Although the study showed that long-term treatment with immediate-release isradipine did not slow the clinical progression of early-stage PD, it did modestly decrease cumulative levodopa equivalent dose and the time needed for antiparkinsonian treatment (McFarthing and Simuni, 2019;Parkinson Study Group STEADY-PD III Investigators, 2020;Venuto et al, 2021). According to epidemiological studies (Becker et al, 2008;Ritz et al, 2010;Pasternak et al, 2012;Lee et al, 2014) and meta-analyses (Gudala et al, 2015;Lang et al, 2015;Mullapudi et al, 2016), patients treated with DHPs have a reduced risk of PD.…”
Section: Cav12 As a Potential Drug Target In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Another more recent example is the calcium channel blocker isradipine. The phase 3 STEADY-PD clinical trial results indicated that this treatment had no impact on the progression of PD in newly diagnosed individuals [20], but recent post-hoc analysis of the phase 3 clinical trial data has provided some evidence to support a re-examination of this agent [21]. Accordingly, a similar reanalysis is now being conducted on the earlier Phase II clinical data.…”
Section: The "In-betweeners"mentioning
confidence: 99%